A vinyl flanked difluorobenzothiadiazole–dithiophene conjugated polymer for high performance organic field-effect transistors. Issue 7 (31st January 2018) - Liang, Xianfeng; Sun, Wandong; Chen, Yanlin; Tan, Luxi; Cai, Zhengxu; Liu, Zitong; Wang, Lin; Li, Jing; Chen, Wei; Dong, Lichun
Abstract : A vinyl flanked conjugated polymerPTFBTV exhibits a hole mobility up to 2.0 cm 2 V −1 s −1 containing possible C–H⋯F hydrogen bonds Abstract : Fluorine containing conjugated polymers have been widely applied in high performance organic solar cells, but their use in field-effect transistors is still quite limited. In this work, a conjugated polymerPTFBTV based on difluorobenzothiadiazole (DFBT) and dithiophene was synthesized, utilizing multiple vinylene as linkers. The polymer exhibits a relatively high hole mobility up to 2.0 cm 2 V −1 s −1 compared with the reported DFBT–oligothiophene based polymers, yet its structural complexity is much simpler. The polymer thin film exhibits a typical 'face on' molecular orientation. A single crystal of its monomer revealed a non-covalent intramolecular contact between fluorine and the neighbouring proton, which strengthens the backbone co-planarity. Meanwhile an intermolecular F⋯F contact was also observed, which might cause rather scattered lamellar crystallinity forPTFBTV in the solid state.